1997
DOI: 10.1006/viro.1997.8506
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Amino-Terminal Extracellular Domain of CXCR-4 in Human Immunodeficiency Virus Type 1 Entry

Abstract: We have studied the role of the N-terminal extracellular domain of the human immunodeficiency virus type 1 (HIV-1) coreceptor, CXCR-4, in the entry and fusion of syncytium-inducing strains of HIV-1. Progressive deletions were introduced in the N-terminal extracellular domain of CXCR-4 and the effect on infection by different isolates was tested. Infection of cells expressing the different CXCR-4 deletion mutants by HIV-1 LAI and 89.6 was reduced only about twofold. In contrast, the HIV-1 GUN-1 and RF isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
2
2

Year Published

1997
1997
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 53 publications
7
87
2
2
Order By: Relevance
“…They argued, however, that non-N-linked-glycosylated CXCR4 mediated R5 HIV-1 entry much less efficiently (100-1000-fold) in comparison to X4 HIV-1. Furthermore, other groups could not detect any alteration in entry of X4 [142,149,150], X4R5 [149] or R5 HIV-1 [150] isolates upon analysis of various CXCR4 mutants with replaced Nlinked glycosylation sites, although Thordsen et al also observed a slight increase in X4R5 infection under these conditions [150]. The apparent discrepancy of these findings might be partly explained by the experimental settings (cells, HIV isolates, infection assays, antibodies used for CXCR4 detection) as well as by the CXCR4 mutants tested (single N 11 versus double N 11 /N 176 substitutions and the type of residue replacing the N residue, such as Q, I or A) [146].…”
Section: Impact Of Change In Receptor Outlook By Glycosylation and Sumentioning
confidence: 90%
See 1 more Smart Citation
“…They argued, however, that non-N-linked-glycosylated CXCR4 mediated R5 HIV-1 entry much less efficiently (100-1000-fold) in comparison to X4 HIV-1. Furthermore, other groups could not detect any alteration in entry of X4 [142,149,150], X4R5 [149] or R5 HIV-1 [150] isolates upon analysis of various CXCR4 mutants with replaced Nlinked glycosylation sites, although Thordsen et al also observed a slight increase in X4R5 infection under these conditions [150]. The apparent discrepancy of these findings might be partly explained by the experimental settings (cells, HIV isolates, infection assays, antibodies used for CXCR4 detection) as well as by the CXCR4 mutants tested (single N 11 versus double N 11 /N 176 substitutions and the type of residue replacing the N residue, such as Q, I or A) [146].…”
Section: Impact Of Change In Receptor Outlook By Glycosylation and Sumentioning
confidence: 90%
“…Out of the 2 potential N-glycosylation sites, only N 11 was concluded to be efficiently glycosylated, whereas the likely unglycosylated N 176 residue might support the three-dimensional structure of CXCR4 [144][145][146][147]. In the absence of Nglycans, the expression levels of CXCR4 remained mostly unaffected [142,[146][147][148][149][150], besides some minor increases [146] or decreases [144,149,150] which might be partly accountable to the detection efficiency of conformation-specific antibodies [135,142,151]. Notably, combined replacement of both potential N-linked glycosylation sites (N 11 Q/N 176 D) of CXCR4 led to the complete disruption of the epitope for the routinely used 12G5 monoclonal anti-CXCR4 antibody [142].…”
Section: Impact Of Change In Receptor Outlook By Glycosylation and Sumentioning
confidence: 99%
“…The NH 2 terminus was the first domain proposed to play a role in coreceptor function from studies showing NH 2 -terminal reactive polyclonal antibody blocking of fusion and virus entry (35). A second report demonstrated that the NH 2 terminus was indeed critical for some isolates yet not the sole element deemed important (52), while additional studies highlighted the importance of other domains, primarily ecl-2, in coreceptor activity (53,54). We have recently shown an importance of negatively charged glutamic acid residues in the NH 2 terminus, as well as some additional charged residues in the extracellular loops, for X4 Env coreceptor activity (12).…”
Section: Charge Introduction Into Ecl-2 and The Impairment Of Ccr5mentioning
confidence: 99%
“…The mechanism of this inhibition is not yet known but most probably involves steric blockade of the co-receptor by the ligand. Alternatively, chemokine-mediated inhibition of HIV entry may be due to downregulation of the receptor on the surface of permissive cells (17).…”
mentioning
confidence: 99%